THE CORRELATION OF EMPLOYEE EFFICIENCY AND ASSET GROWTH: CONVENTIONAL VS ISLAMIC BANKS IN INDONESIA FROM 2010 TO 2016 - Khootimah, Chusnul; Faturohman, Taufik (Journal of Business and Management, 2017)
Abstract - There is no compatibility between the condition of the market share with its balance sheets and growth. According to Otoritas Jasa Keuangan (OJK), there is a slowing growth in Islamic banks. There is therefore a need for authorities to be aware of strategic issues that may inhibit the growth of Islamic banks in Indonesia. One of the strategic issues is the lack of human resources in Islamic banks, if we compare it to conventional banks. The aim of this study is to compare the efficiency of conventional and Islamic banks and the correlation of the efficiency and the asset growth from 2010-2016. The Variable Return to Scale (VRS) Data Envelopment Analysis (DEA) application is used to measure the efficiency. This measurement is based on the output orientation. For determining the significant difference between the efficiency of conventional bank and that of Islamic ones, Mann-Whitney test is employed. To determine the correlation between the efficiency and the asset growth of those two types of bank, Spearman correlation is used. The efficiency measurement is based on employee efficiency, which is calculated by considering the input and the output. Related to the input, the variables include number of employees and personnel expenses. For the output, those variables are loans, total deposits and Net Income Before Tax (NIBT). Â The findings show that conventional banks have higher average of efficiency score than that of Islamic banks in 2010-2016 periods. Except in 2014, there is no statistical difference between Islamic and conventional banks. The statistical significant difference in the 2014 period shows that the technical efficiency of conventional banks is higher than that of Islamic banks. The findings indicate that the performance of Islamic banks is lower compared to the performance of conventional banks. Using Spearman correlation test, it shows that there is no correlation between the employee efficiency and the asset growth of all of those banks. The findings indicate that the employee efficiency is not the factor for increasing the asset growth of both conventional and Islamic banks. Because of that, the Islamic banks are as competitive as those conventional counterparts.Â  It is therefore expected that the Islamic banks can increase their number of customers/market share. Because this study only considers employee efficiency, it is suggested that future research is directed to evaluate efficiency by considering other stakeholders. Keywords: Islamic Bank, Conventional Bank, Employee Efficiency, Coefficient Correlation, Asset Growth.